Crew Position-Based Assessment of Fishermen’s Knowledge Needs in The Coastal Districts of Tamil Nadu - Dani Glenn, V; Arul Oli, G; Lloyd Chrispin, C; Durairaja, R (Indian Journal of Extension Education, 2025)
The study conducted in 2025 (January to May) examined the knowledge needs of fishermen in Tamil Nadu, focusing on their roles within the fishing crew: Skippers/Drivers, Net Haulers, and Helpers. Tamil Nadu, with its extensive coastline, plays a vital role in India’s marine fisheries, supporting millions of fishermen. The study identified key knowledge gaps in areas such as modern navigation technologies, sustainable fishing practices, and gear handling. A total of 150 fishermen were surveyed from coastal districts, including Nagapattinam, Ramanathapuram, Thoothukudi, and Kanyakumari, using a structured questionnaire. The findings indicate that Skippers/Drivers are generally proficient in knowledge and require less training, whereas Net Haulers and Helpers exhibit a higher need for knowledge in technology, sustainability, and gear management.
Keywords: Knowledge needs; Crew-specific training; Skipper; Net hauler; Helper; Training need; Fishermen